Coleções de livros de bolso no Brasil: notas sobre a Biblioteca Universal Popular - Ribeiro, Ana Elisa (2020)
In this work, we have focused in at least two elements of edition that are crucial to the understanding of the modes of production and the circulation of books in Brazil. These are the notions of "popular book" and "pocket book", both closely related to each other and also to production and sales strategies, book formats, book design and certain literary genres or "bookstore" genres. For the purposes of conceptual discussion and analysis of editorial practices, we will deal here, with the Biblioteca Universal Popular (Universal Popular Library). This is a collection of paperbacks published in Brazil between 1963 and 1968 by Editora Civilização Brasileira, one of the most important publishing houses in activity at that time. Another relevant aspect of the present study is the recomposition of the catalog of this collection, which represents one of the many attempts of Brazilian publishers to approach the pocket book market through the edition of low cost books with a wide circulation. The collection and organization of the information presented here are based on investigations in private libraries and in various websites, especially in the online collection of Fundação Biblioteca Nacional and in the website of Estante Virtual.